1994
DOI: 10.1007/bf00203885
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of trace metal concentrations in the digestive gland of the Mediterranean mussel Mytilus galloprovincialis: Comparison between a polluted and a non-polluted site

Abstract: Seasonal changes in metal (Cu, Fe, Mn, Pb, and Zn) concentrations were observed in the digestive gland of the Mediterranean mussel, Mytilus galloprovincialis, from both a polluted and a non-polluted population. Digestive gland of mussels from the polluted site showed metal concentrations appreciably higher than in non-polluted organisms, especially for Pb (up to 160 micrograms/g d.w.), Mn (up to 300 micrograms/g d.w.), and Fe (up to 8,500 micrograms/g d.w.), whereas the two populations showed maximum mean valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
2
8

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 30 publications
5
41
2
8
Order By: Relevance
“…Temporal variation of digestive gland mass is under influence of food availability and reproductive cycle. Since gonadic tissue penetrates into the digestive gland (Regoli and Orlando, 1993), two tissues cannot be separated by dissection (Regoli and Orlando, 1994). Lower concentrations of trace metals in the gonadic tissues (George and Coombs, 1977;La Touche and Mix 1982;Lobel and Wright, 1982) cause "biological dilution" of trace metal concentrations in the digestive gland.…”
Section: Temporal Variations Of Digestive Gland Mass Cytosolic Mt Anmentioning
confidence: 99%
“…Temporal variation of digestive gland mass is under influence of food availability and reproductive cycle. Since gonadic tissue penetrates into the digestive gland (Regoli and Orlando, 1993), two tissues cannot be separated by dissection (Regoli and Orlando, 1994). Lower concentrations of trace metals in the gonadic tissues (George and Coombs, 1977;La Touche and Mix 1982;Lobel and Wright, 1982) cause "biological dilution" of trace metal concentrations in the digestive gland.…”
Section: Temporal Variations Of Digestive Gland Mass Cytosolic Mt Anmentioning
confidence: 99%
“…Besides physico-chemical properties of the seawater, other factors related with the reproductive stage of mussels could also affect metal concentrations in the digestive gland (Regoli and Orlando 1994, Raspor et al, 2004, Ivanković et al, 2005. Therefore, the general trend of higher concentrations of cytosolic metals in March than in August as it was reported in this study for Cu, Cd and Zn (Table 3) could also be related with the possible influence of reproductive status.…”
Section: Discussionmentioning
confidence: 99%
“…In our knowledge cytosolic distribution of metals was not investigated with reference to seasonality. Yet, it is known that the level of total tissue and cytosolic metals show a seasonal variability dependent on the abiotic and biotic factors even when the environmental concentrations of metals remain unchanged (Regoli and Orlando 1994, Raspor et al, 2004, Ivanković et al, 2005. Similarly, it is found that biomarkers are also affected by seasonality (Ivanković et al, 2005; Bocchetti and Regoli , 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 5 organism.…”
Section: Introductionmentioning
confidence: 99%
“…No caso de estocagem, entende-se que o organismo faça um investimento metabólico para regular a concentração de alguns metais ("reguláveis"), conforme é a sua demanda metabólica de um dado elemento, e a sua biodisponibilidade no ambiente (Depledge & Rainbow, 1990). O zinco pode ser citado como exemplo de metal regulado por bivalves (Regoli & Orlando, 1994), o que dificulta avaliar a contaminação ambiental através dos dados de bioacumulação deste elemento em bivalves.…”
Section: Metaisunclassified